On the performance of hybrid active-passive damping treatments mechanisms for vibration control of beams using adaptive feedforward strategies - C. M. A. Vasques (2006)
This paper concerns the adaptive feedforward control of vibration of a freely supported beamwith two distinct surface mounted hybrid active-passive damping treatments. The first configurationconcerns the use of an Active Constrained Layer Damping (ACLD) patch alone, wherethe piezoelectric constraining layer is actively utilized to increase the shear deformation of thesandwiched passive viscoelastic layer and at the same time to apply forces and moments intothe structure, which will balance the power flows into the structure, and is denoted by ACLDconfiguration. The second configuration regards the use, as an active element in the control,of a piezoelectric patch alone, denoted by Active Damping (AD), and since the constraininglayer of the ACLD treatment also bonded on the other side of beam is not actively utilized,a Passive Constrained Layer Damping (PCLD) treatment is utilized in combination with AD,and an AD/PCLD configuration is considered. A finite element (FE) model of the beam withthe damping treatments is used for the simulation of the adaptive feedforward controller whichis also tested in real-time. The aims are to compare the predicted and measured damping performancesof the two treatments, in terms of vibration reduction, control effort, stability androbustness when a filtered-reference LMS algorithm is used to cancel the effects of a broadbandvoltage disturbance applied into a third surface mounted piezoelectric patch which is used toexcite the beam.